MECHANICAL VENTILATION IN THE MANAGEMENT OF GUILLAINBARRE SYNDROME IN ICU - Gilani, Syed Mushtaq (Journal of Ayub Medical College Abbottabad, 2000)
An early ventilator or respiratory’ assistor was invented by Janeway1 in 1913. Crafoord-a thoracic surgeon reported on his Spiropulsator along with Anderson2 launching the ventilator for intermittent positive pressure ventilation (IPPV)in the intensive therapy unit. Under the guidance of Prof. Macintosh and his department at oxford anaesthetists became clinicians who best understood the ventilation and so began the anaesthetist’s involvement in ICU. Guillaine-Barre syndrome, noted first by Landy in 1859 and subsequently by Guillain, Barre and Strohl in 1916, may best be described as an Acute Inflammatory’ Polyradiculoneuropathy 3 with a prevalence of approximately. 1.5 per 100,000 of population. It may affect individuals of any age4. The disease is self-limiting, the main life threatening problem in AIP is acute respiratory- failure resulting from respiratory’ muscle weakness and may need artificial ventilation. What follows is our experience of mechanical ventilation of two cases of AIP (Guillain- Barre syndrome) in the ICU of SK Institute of Medical Sciences, Srinagar (Kashmir).